2000
DOI: 10.1038/35007091
|View full text |Cite
|
Sign up to set email alerts
|

ATM phosphorylates p95/nbs1 in an S-phase checkpoint pathway

Abstract: The rare diseases ataxia-telangiectasia (AT), caused by mutations in the ATM gene, and Nijmegen breakage syndrome (NBS), with mutations in the p95/nbs1 gene, share a variety of phenotypic abnormalities such as chromosomal instability, radiation sensitivity and defects in cell-cycle checkpoints in response to ionizing radiation. The ATM gene encodes a protein kinase that is activated by ionizing radiation or radiomimetic drugs, whereas p95/nbs1 is part of a protein complex that is involved in responses to DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
503
4
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 716 publications
(536 citation statements)
references
References 24 publications
23
503
4
6
Order By: Relevance
“…Several studies showed that the expression of S343A mutant Nbs1 in NBS cells resulted in partial defects in IR-induced S-phase checkpoint activation, radiosensitivity and partial defects in ATM-dependent phosphorylation events including Chk2, SMC1 and FANCD2 (Lim et al, 2000;Buscemi et al, 2001;Nakanishi et al, 2002;Yazdi et al, 2002). Our studies also showed that the MRN complex containing mutant Nbs1 (S343A) failed to stimulate the phosphorylation of Chk2 by ATM although p53 phosphorylation was normal in vitro.…”
Section: Phosphorylation Of Nbs1supporting
confidence: 50%
See 3 more Smart Citations
“…Several studies showed that the expression of S343A mutant Nbs1 in NBS cells resulted in partial defects in IR-induced S-phase checkpoint activation, radiosensitivity and partial defects in ATM-dependent phosphorylation events including Chk2, SMC1 and FANCD2 (Lim et al, 2000;Buscemi et al, 2001;Nakanishi et al, 2002;Yazdi et al, 2002). Our studies also showed that the MRN complex containing mutant Nbs1 (S343A) failed to stimulate the phosphorylation of Chk2 by ATM although p53 phosphorylation was normal in vitro.…”
Section: Phosphorylation Of Nbs1supporting
confidence: 50%
“…The Mre11/Rad50/Nbs1 (MRN) complex has been shown by several groups to be required for the ATM signaling pathway (Lim et al, 2000;Buscemi et al, 2001;Girard et al, 2002;Nakanishi et al, 2002;Yazdi et al, 2002;Uziel et al, 2003). Most of these studies were performed using cells derived from patients with Nijmegen Breakage Syndrome (NBS) or Ataxia-TelangiectasiaLike-Disorder (ATLD), which are caused by hypomorphic alleles of the Nbs1 or Mre11 genes, respectively (Carney et al, 1998;Varon et al, 1998;Stewart et al, 1999).…”
Section: The Role Of the Mrn Complex In Atm Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Once activated it then phosphorylates a series of substrates including Nbs1. Specific phosphorylation of Nbs1 on S287 and S343 plays a role in the activation of the intra-S-phase checkpoint (Lim et al, 2000). Yazdi et al (2002) showed that ATMdependent phosphorylation of Nbs1 was required for phosphorylation of SMC1, implying that Nbs1, presumably as part of the MRN complex, was an adaptor in an ATM/Nbs1/SMC1 pathway controlling the S-phase checkpoint.…”
Section: Perspectivementioning
confidence: 99%